(untitled) (Research, Society and Development, 2022)
The Tropical dry forests cover large regions of the world and have been extensively altered by human activities. This study was aimed at characterizing and comparing the density, diversity and structural parameters of a human-altered secondary dry within an interval of five years of regeneration. Two hundred plots were established in the forest and two monitoring surveys were carried out, with interval of five years between them. All individuals in each plot with diameter at the ground level ≥ 3 cm were measured. After five years, no differences were observed in the number of species. Total density and mean basal area decreased, as a result of the maturation of the forest and possibly due to a prolonged drought in 2012. In 2008, the total basal area was 10.59 m².ha-1, increasing to 11.01 m².ha-1 in 2013. The mean height of the community did not increase significantly, from 3.59 m in 2008 to 3.65 min 2013. The number of individuals in the larger diameter classes reduced between 2008 and 2013, while the opposite was observed for smaller classes. Some structural parameters increased or decreased depending on the group of species analyzed and there was still a group that did not present significant changes. Therefore, age since abandonment can affect the regeneration process and the resilience of the forest. We realized, the speed in which these alterations occurred in an interval of five years can be considered slow and changes in the recovery process of a 16-year-old forest may not be detected.